2014
DOI: 10.1098/rspa.2013.0605
|View full text |Cite
|
Sign up to set email alerts
|

Non-steady-state heat conduction in composite walls

Abstract: The problem of heat conduction in one-dimensional piecewise homogeneous composite materials is examined by providing an explicit solution of the one-dimensional heat equation in each domain. The location of the interfaces is known, but neither temperature nor heat flux is prescribed there. Instead, the physical assumptions of their continuity at the interfaces are the only conditions imposed. The problem of two semi-infinite domains and that of two finite-sized domains are examined in detail. We indicate also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 7 publications
1
59
0
Order By: Relevance
“…Therefore, in combination with the general strategy put forward in this article, problems of Wiener-Hopf type arising for those equations should also be amenable to an analysis akin to that given here. It is interesting to note that a recent study of non-steady state heat conduction with composite walls [24] has several features in common with our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in combination with the general strategy put forward in this article, problems of Wiener-Hopf type arising for those equations should also be amenable to an analysis akin to that given here. It is interesting to note that a recent study of non-steady state heat conduction with composite walls [24] has several features in common with our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Fokas method [1,2] such solutions may be constructed. This has been done in the case of the heat equation with n interfaces in infinite, finite, and periodic domains as well as on graphs [3][4][5][6][7]. The method has also been extended to dispersive problems [8,9], and higher order problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, H 15) and the Cauchy integral is explicitly evaluated by the theory of residues. Alternatively, this splitting can be obtained by representing the function H(s) as a sum of n integrals similar to (2.8) and then removing the poles.…”
Section: Matrices With Almost Periodic and Rational Entriesmentioning
confidence: 99%
“…In §2, we consider the heat equation for an infinite rod u t = a 2 (x)u xx + g(x, t) with a piecewise constant diffusivity a(x). The Fokas method [13] was recently applied [14,15] to the heat equation in a ring and a rod. Deconinck et al [15] found an exact solution in the homogeneous case, g ≡ 0, when the diffusivity is a piecewise constant function, and (i) the rod is finite and the diffusivity has one or two points of discontinuity and (ii) the rod is infinite and the function a(x) is discontinuous either at 0 and ∞ or at two finite points and infinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation